Social Security in Latin America: Pressure groups, stratification, and inequality - Mesa-Lago, Carmelo (Pittsburgh: University of Pittsburgh Press, 1978)
This book is a compilation of legislation, statistics, and technical reports; discussion, analysis, and writing on the subject of social security in Latin America with case studies from Chile, Uruguay, Peru, Argentina, and Mexico.
Includes bibliographical references and index.
ne 14/05/2018
Loan
Keywords: Social security; Latin America